The Function of Tranexamic Acid to Prevent Hematoma Expansion After Intracerebral Hemorrhage: A Systematic Review and Meta-Analysis From Randomized Controlled Trials - Yan, Zeya; Chen, Shujun; Xue, Tao; Wu, Xin; Song, Zhaoming; Wang, Zongqi; Chen, Zhouqing; Wang, Zhong (Frontiers in Neurology, 2021)
Objectives: The clinical results caused by spontaneous intracerebral hemorrhage (ICH) are disastrous to most patient. As tranexamic acid (TXA) has been proved to decrease the influence of ICH, we conducted this research to explore the function of TXA for the prognosis of ICH compared with placebo. Methods: We searched MEDLINE, Embase, Cochrane Library, and Clinicaltrials.gov for randomized controlled trials (RCTs) that were performed to evaluate TXA vs. placebo for ICH up to February 2021. The data were assessed by Review Manager 5.3 software. The risk ratio (RR) and mean difference were analyzed using dichotomous outcomes and continuous outcomes, respectively, with a fixed effect model. Results: We collected 2,479 patients from four RCTs. Then, we took the change of hematoma volume, modified Rankin Scale (mRS), and adverse events as evaluation standard of the treatment for ICH. Through statistical analysis, we found that there is no obvious hematoma expansion effect after the application of TXA (RR = 1.05), and we proceeded the quantitative analysis of percentage change in hematoma volume from baseline, indicating that TXA could inhibit the expansion of hematoma volume (RR = −2.02) compared with placebo. However, according to the outcomes of mRS (0–1, RR = 1.04; 0–2, RR = 0.96), TXA cannot improve neurological functional prognosis. As for the security outcomes—mortality (RR = 1.02), thromboembolic events (RR = 0.99), neurological deterioration (RR = 0.92), infection (RR = 0.86), and craniotomy (RR = 0.41), there seems exist no statistical difference between TXA and placebo. Conclusions: TXA has an advantage in the aspect of preventing hematoma expansion compared with placebo for ICH, but cannot illustrate the efficacy of TXA in improving neurological functional prognosis, which still needs more researches with large sample sizes. Moreover, for safety, we did not find obvious statistical difference between TXA and placebo.